Membrane Bioreactors for Pharmaceutical Applications: Optically Pure Enantiomers Production - Piacentini, Emma; Mazzei, Rosalinda; Giorno, Lidietta (Current Pharmaceutical Design, 2017)
In biological systems, recognition at molecular level is governed by chiral interactions. Therefore, optical isomers have very different effect in natural systems. For example, one can have beneficial effect while the other can be very harmful. For these reasons, chiral drugs nowadays are mainly admitted in the optically pure form. Given these requirements, it is clear why demand for chiral drugs has grown dramatically and the singleenantiomer drug segment has become an important part of the overall pharmaceutical market. As a consequence, the development of new chiral separation techniques is a very hot topic in both academic research and industrial innovation. Membrane bioreactors have proven their feasibility in the production of optically pure enantiomers by combining enantiospecific biochemical reactions with mass transport through membranes. The principles and the applications of enantioselective membrane bioreactors in kinetic resolution for pharmaceutical applications will be discussed. Various membrane bioreactors configurations and operation mode will be illustrated. The type of enzymes utilized to produce chiral drugs or their intermediates will be also reported. Multistep syntheses, conducted in sequential reactions catalysed by spatially aligned biocatalysts, as promising technology for the synthesis of fine chemicals will be highlighted.
Keywords: Membrane bioreactor